Le Lesotho Highland Water Project, ou le retour de la grande hydraulique en Afrique australe - David Blanchon (Bulletin de l’Association de Géographes Français)
The Lesotho Highlands Water Project (LHWP) is the last major international interbasin transfer system that has been planned during the apartheid era. According to the 1986 treaty between Lesotho and South Africa, a chain of major dams should have been constructed in the high mountains of the landlocked kingdom in order to transfer water via tunnels to the water-stressed metropolitan region of Gauteng.The project aroused fierce environmental and social criticism, but the construction process went on after the end of apartheid. But the ANC leaders, who were against the project in the 1980s, decided to build only two (phase 1a and 1b) of the five planned phases.According to the new South African water policy, water demand management was a national priority and all the big dams and IBT should have been abandoned. This was the official policy during the first years of the 21st century. But as new problems, such the Acid Mine Drainage (AMD) issue, emerged, South Africa and Lesotho decided to build a new major dam in Lesotho, at Polihali, in order to transfer more water.This paper examine the reason of the “return of the LHWP”, its meanings and its consequences on the Southern African hydropolitical complex.